Reaching Innu and Atikamekw Youths in their communities: Future Healthcare Professionals Working Together - Moderie, Christophe; Davidson, William; Filiatrault, Sandrine; Groulx, Geneviève; Brault, Isabelle; Clar, Monique; Drouin, Éric (2017)
Background Mini-Schools of Health are held since 2011 in indigenous communities by the Université de Montréal's Faculty of Medicine and the student's Groupe d’intérêt en santé autochtone (GISA). These events take place in schools and allow health sciences and social work undergraduates to discuss health issues with Innu and Atikamekw youths. The Mini-School aims to promote school perseverance, a healthy lifestyle, and build cultural competence in undergraduates. Mini-School participants come from thirteen different undergraduate programs and multidisciplinary collaboration is facilitated by commonly addressing complex indigenous health issues. Method Mini-Schools take place three times a year. The communities of Wemotaci and Manawan are visited in the fall or spring, during a one-day trip. The third Mini-School takes place in June during a full week. Innu communities located in the Côte-Nord region, notably Ekuanitshit and Nutashkuan, are visited. Between 250 and 300 students are met yearly in each community by forty undergraduates. Recruitment of undergraduates is managed by the GISA and the Interprofesionnal Student Council. Pre-departure training is mandatory to provide knowledge about the community’s reality and promote respectful and culturally informed interactions. Interdisciplinary exchanges are initiated during the training as participants from various programs bring different perspectives in the discussion. Mini-Schools are held a few days after training and allow undergraduates to join students in class to discuss various themes. In elementary schools, the pleasure of physical activity and healthy eating are addressed, as well as general well-being. In high schools, emphasis is given to complex health issues such as mental health, drug abuse and sexual health. At the same time, other participants host kiosks in the gymnasium and share with students their passion about their future profession. Interactive games are organized to present career prospects such as: nurse, doctor, social worker, pharmacist, nutritionist, optometrist, dentist, audiologist and physiotherapist. Mini-Schools are concluded by a community dinner and a visit to the healthcare facility. Outcomes Since the introduction of the Mini-Schools in 2011, more than five hundred undergraduates have taken part in the project. Medical students were the only participants at first but the potential for interprofessional education was soon perceived and students from other programs, mainly in health sciences but also information sciences, were invited to join. Participants from various study programs have developed strong friendships and have kept in touch by organizing social and academic activities. Positive feedback is commonly reported from undergraduates and students. In-person meetings with school administrations and teachers revealed a great level of community satisfaction with these activities. The good reception of the Mini-Schools suggests a short-term positive impact. The long-term impact is yet difficult to measure since it will require data such as the evolution of the graduation rate and the number of future health professionals from these communities. Conclusions The immersive and intense experience of the Mini-School might be prone to enhance readiness for interprofessional collaboration among future healthcare professionals. This project also allows rich interactions in the communities that hopefully will encourage students to believe in their dream and to become healthcare professionals.